The use of blogs to improve writing skills in students of 10th grade in a public high school of Loja city - Jiménez Acaro, Clara Juliana (2023)
The utilization of blogs as a language learning instrument has experienced a surge in popularity and demonstrated encouraging outcomes in recent times. The objective of this study is to examine the utilization of blogs as a means to enhance the English as a Foreign Language (EFL) writing abilities of 10th- grade students enrolled in a public high school located in Loja City, Ecuador. The study encompassed a sample of 10th-grade students attending a public high school located in Loja, Ecuador. The participants were between the ages of 14 and 15 and were engaged in English language learning at an A2 competence level, as defined by the Common European Framework requirements. Despite encountering difficulties in writing, they had a commendable disposition towards learning. The results indicated a statistically significant improvement in the writing skills of the students, implying that blogs served as an effective tool for enhancing their proficiency in English writing.